Analyzing trade integration in North African markets: A border effect approach - Chebbi, Houssem Eddine; Abbassi, Abdessalem; Tamini, Lota D. (International Food Policy Research Institute, 2016)
This paper uses the border effect estimate from a gravity model to analyze the level of market trade integration among Algeria, Egypt, Mauritania, Morocco, and Tunisia from 2005-2012. We analyze total trade as well as trade in agricultural and industrial products. The border effect estimates show that crossing a national border within these North African countries induces a trade-reduction effect. The highest effect is for Algeria, with total trade being reduced by a factor of 5 in 2011-2012, while the lowest effect is for Tunisia, with the total trade being reduced by a factor of 2 in 2011-2012. Our results also show that the border effect is stable over time. The mean value masks differences that are quite substantial in market integration when considering agricultural products or industrial products, the borders effects being lower for the latter. For industrial products in 2011-2012, the highest border effect is in Tunisia, with a factor of 3.3, and the lowest border effect is for Morocco with a factor of 1.9. For agricultural products in the same period, the highest border effect is in Algeria, with a factor of 5.9, and the lowest border effect is in Egypt, with a factor of 2.9. Finally, the equivalent tariffs implied by the estimated border effects are not implausible compared to the actual range of direct protection measures. Integration of the North African market should be pursued by improving structural policies to improve trade efficiency and reap the benefits of international trade.